How Are Egyptian Agricultural Students Preparing for a Career? - Ramjee P Ghimire; D. Hashini Galhena Dissanayake; Paul Ebner; Nanda Joshi; Leah Thompson (Journal of International Agricultural and Extension Education, 2021)
Egypt has made substantial progress in access to education. However a high unemployment rate among university graduates and employers being unable to find a skilled workforce are of great concern. A pragmatic approach for education that enables student to participate in career preparation activities in and outside the classrooms and prepare them for a job following their graduation is of paramount importance. Soliciting opinions from undergraduate students and professors in five agricultural universities and employers from major agricultural industries in Egypt this study aimed to identify student participation in career preparation activities, ascertain major sources for career advice and information about their prospective careers and preparation for those careers. The findings revealed that students had limited opportunities to practice in their career skill-building through their coursework activities. For a majority of the students, professors and university graduates were the primary sources for career advice. Students seldom visited career services offices and did not quite utilize their services, but frequently browsed websites of potential employers. Career advising services appeared to be below the students’ expectations across the universities. Strategies and policies are needed to strengthen career advisory services at universities to improve graduates’ chances of obtaining meaningful employment in their fields of study.
Keywords: Career preparedness; sources of career advice; undergraduate students; skills